(untitled) - Woodson, Jacqueline; Espinosa, Leo (New York, 2022)
"A group of kids celebrate the joy and freedom of summer on their Brooklyn block"--
Ages 5-8
Keywords: Fiction; Play; Fiction; Summer; Play; Juvenile fiction; Summer; Juvenile fiction; Brooklyn (New York, N.Y.); Juvenile fiction; Brooklyn (New York, N.Y.); Fiction; Picture books